2020
DOI: 10.1362/147539220x16003502334226
|View full text |Cite
|
Sign up to set email alerts
|

Investigating loyalty through CSR: The mediating role of brand image and brand trust

Abstract: The purpose of this study is to investigate the effect of corporate social responsibility (CSR) activities on brand image, brand trust, brand loyalty, and purchase intention, based on consumers' perceptions in the context of the retail hypermarkets industry within the Egyptian market. To address the objectives of the study, a quantitative research methodology was used; the data were collected through a questionnaire, resulting in 403 valid responses from customers. The collected data were analysed using SPSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In contrast, companies that engage in authentic CSR activities have a greater influence on consumers’ perceptions of their brands (Afzali and Kim, 2021). Consequently, consumers prefer to purchase trustworthy brands from companies that care about society (Abd-El-Salam, 2020; Sen and Bhattacharya, 2001). On the other side, the CSR practices of service companies enhance customer trust, which increases customer loyalty in the insurance industry (Iglesias et al , 2020).…”
Section: Discussion and Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, companies that engage in authentic CSR activities have a greater influence on consumers’ perceptions of their brands (Afzali and Kim, 2021). Consequently, consumers prefer to purchase trustworthy brands from companies that care about society (Abd-El-Salam, 2020; Sen and Bhattacharya, 2001). On the other side, the CSR practices of service companies enhance customer trust, which increases customer loyalty in the insurance industry (Iglesias et al , 2020).…”
Section: Discussion and Theoretical Contributionsmentioning
confidence: 99%
“…Authentic CSR activities help companies in developing favorable brand attitudes (Kim and Lee, 2020), and these authentic CSR activities may also assist them in developing brand trust. Previous research has shown that perceived CSR actions can benefit society’s well-being and improve consumer trust in brands (Abd-El-Salam, 2020; Sharma and Jain, 2019). However, the literature on the effect of authentic CSR actions on brand trust is scarce.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, when an organization communicates its CSR activities on social media with consumers, they feel admired for being the consumers of such organization [75]. This feeling of admiration promotes consumers to develop a higher level of loyalty for a socially responsible organization [76]. There are different researchers in the extant literature who established that CSR activities of an organization are helpful in developing positive emotions on the part of consumers [59,77,78].…”
Section: Hypothesis (H1) Csr-s Positively Relates To Consumers' Purcmentioning
confidence: 99%
“…Corporate Social Responsibility refers to initiatives “that appear to further some social good, beyond the interests of the firm and that which is required by law ( McWilliams and Siegel, 2001 , p. 117).” Companies build strategies to generate maximal profit as well as to integrate social values and social responsibilities into their strategies ( Abd-El-Salam, 2020 ). CSR has been identified as an essential element that embeds companies in society and means that they cannot be considered separately ( McWilliams and Siegel, 2001 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there has been a lack of empirical studies on CSR perceptions among customers and the consequences of customer behavior ( Abd-El-Salam, 2020 ). In this regard, this study focused on voluntary CSR activities for core stakeholders in the context of the restaurant industry.…”
Section: Literature Reviewmentioning
confidence: 99%